Ochre use at Sibudu Cave and its link to complex cognition in the Middle Stone Age - Hodgskiss, Tamaryn Penny (My University, 2014)
Ochre is found at many Middle Stone Age (MSA) sites and its use is often attributed by archaeologists to enhanced mental abilities and symbolism. However, the links between the visible uses of ochre, cognition and symbolism have not been clearly demonstrated. Here it is argued that by understanding ochre processing technology and some of the stages involved in using ochre, one can determine the skill, knowledge and cognitive abilities required to execute those activities. In order to understand the usetraces found on ochre, and to enable the identification of them, as well as the types of ochre used, experiments were first performed with geological ochre specimens. Ochre pieces collected from the Sibudu surrounds were used experimentally for a variety of grinding, scoring and rubbing activities. All use-traces created on the ochre piece during an activity were macro- and microscopically examined, recorded and compared. Experimental ochre pieces ground against a coarse or fine-grained slab develop parallel striations. Grinding results in significant changes to the surface shape of the ochre, and often results in faceted edges. Scoring can be performed with the intention to create powder, or to create a design. The incisions created from scoring often do not reach all the edges of the used surface and they regularly have frayed terminations. A frayed incision termination shows that the incision was created by multiple scoring strokes. When ochre is scored to manufacture powder the incisions that are generated are parallel groups of grooves with erratically oriented grooves as well. Grooves created through both grinding and scoring have microstriations within them and they show a range of profile shapes. The most common use-wear from rubbing ochre on soft materials is smoothing, edge rounding and polish. Microstriations and metallic lustre occasionally form during rubbing. The collection of utilised experimental ochre formed a comparative collection for the examination of the Sibudu ochre. The main body of this research comprises a study of the Middle Stone Age ochre assemblage from Sibudu, KwaZulu-Natal, South Africa. Sibudu has a large Middle Stone Age ochre assemblage of over 9000 pieces of ochre from layers dating between ~77 ka and ~37.6 ka. All pieces were examined to determine the types of ochre used and to inspect all use-traces present on the pieces. The assemblage comprises 5449 ochre pieces iv >8 mm, including 682 pieces with markings from use. The pre-Still Bay (~77 ka) and Howiesons Poort (~65–62 ka) layers have the highest percentage of utilised pieces. Bright-red ochre was preferentially selected for use throughout most of sequence. There is evidence of the preferential selection of specific types of ochre for use in the Sibudu assemblage. Shale and pieces with medium hardness values are common throughout the sequence. Grain sizes change through time – pieces with clayey grain sizes are favoured during the Still Bay and Howiesons Poort, whereas silty grain sizes are preferred in the younger Middle Stone Age occupations. High frequencies of bright-red amongst the utilised pieces, coupled with high frequencies of yellow or orange pieces with no evidence of use, suggest that colour choices were deliberate and not a product of postdepositional heating. Chemical analysis of a sample of utilised pieces indicates that they all contain iron, silicon, aluminium and calcium; many pieces contain hematite and some contain maghemite. Use-traces were divided into activity categories, based on experimental results. Combined grinding and rubbing is the most frequent activity for which ochre pieces were used. Grinding and rubbing use-wear also occurs independently on many pieces. Scored pieces are rare, but are more frequent in the pre-Still Bay (~77 ka) industry than elsewhere in the sequence. Some of the incisions appear to be deliberate engravings, and parallel lines and fan-like marks are the most often repeated patterns. Use-traces acquired during powder-producing activities predominate, implying a desire to create ochre powder. Powder-producing activities were mainly performed with bright-red pieces, while minimal scoring is mainly present on brown-red pieces. Pieces with mica inclusions are not common, but were frequently used for powder-producing activities. Once the activities performed with ochre were established, thought-and-action sequences, or cognigrams, were constructed. This helped establish the steps involved in each activity and the temporal and physical distance between the commencement of a task to its completion. Inferential sequences were constructed to establish the procedures and knowledge needed to complete an activity, thereby establishing the cognitive prerequisites. Cognitive interpretations are made using the concept of enhanced executive functions of the brain. The construction of the inferential thoughtv and-action sequences showed that the various ways that ochre was used have different cognitive requirements. Powder-production alone is not an indicator of complex cognitive processes, although some planning, foresight and knowledge of materials is required. Some of the powder was used in the creation of hafting adhesives, which is a cognitively demanding process requiring attention-switching ability, response inhibition and abstract thought. Grinding ochre and then rubbing the piece on a soft material for the direct transfer of powder does require some complex mental abilities, such as multi-tasking and switching attention. Scoring a piece of ochre with a sharp tool does not necessitate enhanced executive functions, but some engravings demonstrate foresight, intentionality and an awareness of space and symmetry that may demonstrate abstract thought. This research provides a complete description of the Middle Stone Age ochre assemblage at Sibudu, and establishes the way that ochre was used at the site. This contributes to the debate on the advent of enhanced behaviours in the past by providing insight into the cognitive abilities required by the ochre users. It offers a method of analysing ochre use in the past by drawing on cognitive theory and the visible applications of ochre. Both simple and complex cognitive abilities were required for ochre activities at Sibudu. The requirement for cognitively complex abilities in some of the ochre-related activities at Sibudu suggests that the people living there during the MSA had advanced mental capabilities like modern humans living today. This research shows how ochre use can be employed as a proxy for cognitive capabilities, and can therefore shed light on the evolution of the modern mind.
Keywords: Archaeologists - South Africa - Sibudu Cave.; Mesolithic period.; Symbolism of colors - History.; Cave dwellings - South Africa - KwaZulu-Natal.